Family planning instructor’s performance in the toddler family development program - Simon Sumanjoyo Hutagalung; Dedy Hermawan; Amir Husin (Intelektual Pustaka Media Utama, 2021)
Family planning instructors are vital in implementing the toddler family development program considering their function. This article aims: i) Analyze the performance of family planning instructors in the implementation of the toddler family development program/bina keluarga balita (BKB); ii) Analyse the factors supporting and inhibiting the effectiveness of the performance of family planning instructors in the community. This research used quantitative methods through survey instruments with a population of all family planning instructors which implementing toddler family development program. The pandemic situation has made the data collection process carried out by online questionnaires with Google Forms application. In order to obtain the required data, data collection was carried out through a questionnaire with a sample of 84 respondents. Data analysis was performed through descriptive statistical analysis using MS.Excel and SPSS. The data analysis concluded that the performance of family planning instructors in managing the program is in the good category. In the process approach, effectiveness is shown from the fulfillment of these performance variables in the implementation of the program, so that by looking at the categories in the cumulative analysis that are in the good category.